HERMAPHRODITISM IN COCONUT COLLECTIONS OF ViSCA, LEYTE, PHILIPPINES - T. C. Nunez (International Coconut Community Journal, 1994)
Bisexual button‑like flowers were found in the dwarf cultivars Albuera, Catigan, Coconino, Lingkuranay, Malayan Red, Malayan Yellow and Tacunan as well as in Baybay Tall in varying frequencies. These hermaphrodites differed in size, possessed varying number of fully developed anthers that contained pollen with 46.4 ‑84.1% fertility. knong the big hermaphrodites, their distinct characteristics are partly exposed ovary at inflorescence opening and earlier stigmatic receptivity compared with the normal buttons.